PERANCANGAN APLIKASI PENGOLAHAN DATA NILAI SISWA SEKOLAH DASAR NEGERI 1 JAYA SAKTI MENGGUNAKAN VISUAL BASIC - Puspita, Dian; Yuliana, Eka (JPGMI (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Multazam), 2016)
This research is to design the application of student data processing as supporting in decision making and daily operational requirement, and also to compare the level of effectiveness and efficiency in data processing and presentation of information between current system and proposed application. Research done in matters this is a qualitative descriptive research by conducting a survey of the object of research that is at Primary School Negeri 1 Jaya Sakti Lampung Central using data collection techniques that is Observation (observation), Interview (interview), and Research Library. System created is a database system using Microsoft Visual Basic as its programming language. System testing is performed to test the level of effectiveness and efficiency of the system including the level of accuracy of data, presentation of information and data validation of the proposed application. So that the data processing and presentation of reports in accordance with the expected. The results showed that by using the computerized system in data processing and data collection Student Value is more effective and efficient than the previous system.Â